2022
DOI: 10.29271/jcpsp.2022.08.1083
|View full text |Cite
|
Sign up to set email alerts
|

Saved by the Clot in Superior Vena Cava Injury

Abstract: Penetrating neck injuries (PNIs) can cause injuries to great vessels. Superior vena cava (SVC) injury from a stab to the neck is rare and when it occurs, poses a significant risk of exsanguinating hemorrhage. We report a case of a 17-year female who survived a delayed presentation of five hours after sustaining stab injury to zone 1 of the neck. Her external wound was just above the medial 1/3 rd of the clavicle which resulted in SVC laceration. Mechanism and site of injury along with clinical presentation wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…85.7% patients with SCA in our study had left anterior descending artery disease, a previous study reported this prevalence to be 79.5%. 11 Sudden cardiac arrest is commonly caused by acute coronary syndrome (ACS). Diagnosing ACS is another challenge.…”
Section: Discussionmentioning
confidence: 99%
“…85.7% patients with SCA in our study had left anterior descending artery disease, a previous study reported this prevalence to be 79.5%. 11 Sudden cardiac arrest is commonly caused by acute coronary syndrome (ACS). Diagnosing ACS is another challenge.…”
Section: Discussionmentioning
confidence: 99%